Acquisition of speech accuracy of sentences in children with cochlear implant - das Neves, Anderson Jonas [UNESP]; Moreira Almeida-Verdu, Ana Claudia; Nascimento Silva, Leandra Tabanez do; Mortari Moret, Adriane Lima (Pontificia Univ Catolica Peru, 2020)
Speech accuracy is an indicator for evaluating the language of children with cochlear implant (CI). Verifying the teaching that increases this accuracy and how efficiency measures can be adopted are relevant questions. The current study evaluated the acquisition of speech accuracy, using pictures of scenes as controls. Sentences were employed after equivalence-based instruction. Eight children with CI and who were readers participated in the study. The sentences had the following structure: [subject]-[verb]-[object]. The teaching included selecting pictures and constructing printed sentences, conditionally to dictated sentences. Naming and reading was monitored by multiple probes. Two judges transcribed the participants' vocalizations and the accuracy was measured by the correspondence with target-phonemic units of sentences. All the participants increased the speech accuracy in response to pictures of scenes after the teaching. Acquisition standards were observed and the accuracy was firstly obtained in the terminal portion, followed by the initial portion and, lastly in the medial portion. These results suggest how and under conditions establish the speech accuracy of the sentences in children with CI.
Keywords: cochlear implant; speech accuracy; sentences; teaching; oral language